Perception of the process of inclusion in regular basic education among teachers in the primary level of Lima north - Estrella-Serón, Gina (2020)
The possibility for educational institutions of all levels to seek to consolidate inclusion mechanisms is the ideal of equity in education. For this reason, the present work opted for the non-experimental descriptive design, aimed at comparative analysis of the perception of the inclusion process in two basic level educational institutions in two districts of North Lima. The sample was made up of 120 teachers from the primary education level, to which the adapted questionnaire of indicators of Inclusion -Bristol (2019) was applied, made up of three dimensions: Creating inclusive cultures, with 13 items, Carrying out inclusive policies, with 11 items and Developing inclusive practices with 16 items; which was validated by expert judgment. The results indicated that there were significant differences in the level of perception of the inclusion process between the teachers of both locations, as well as variations in the perception of the dimensions proposed. It was concluded that the existence of differences in the perception of inclusion of the teachers of the two districts has been due to the positions of the teachers regarding the institutional policy and their perception of the inclusion process.